Governing Using Criminal Law: Historicising the Instrumentality of Criminal Law in Ethiopian Political Power - Assefa, Simeneh Kiros; Wotere, Cherinet Hordofa (Bahir Dar University Journal of Law, 2024)
While a constitution vests (limited) power on a government, criminal law may be used to effectively deny power to any contending party (group). This article argues that besides achieving its legitimate ends of prevention of crime, the criminal law is used to govern the country by denying power to contending parties. This is done based on the analysis of the adoption of the respective constitutions, the adoption of the criminal laws and the attending socio-political circumstances of the adoption of the criminal law.Emperor Haile Selassie adopted the 1930 Penal Code on the day of his coronation which is later sanctioned by the 1931 Constitution which makes his power perpetual „divine right‟. When the Provisional Military Government had come to power, it adopted a Special Penal Code to be applied by a Special Courts-Martial, and the PDRE Constitution came only 13 years later. Likewise, as soon as EPRDF came to power, it detained the previous regime officials, both civilian and military, in the first few days. It is only after such action that the Transitional Period Charter was drawn up.